Anterior epitympanic attic antrum space obstruction and symptom onset associated with myringosclerosis in benign chronic suppurative otitis media - Naftali, Zulfikar; ., Suprihati; E., Dharmana; H., Setyawan (International Journal of Research in Medical Sciences, 2020)
Background: The AAA (Anterior epitympanic, Attic, and Antrum) space is the space between the mastoid and middle ear which functions to balance the pressure in both organs (buffer). Pathological tissue in the AAA cavity due to chronic infection would disrupt the buffer function and could change the morphology of the mucosa in the tympanic membrane and middle ear. Obstruction in the AAA space measured subjectively by observing the smoothness of the flow using saline solution has been shown to be associated with a plaque in the tympanic membrane (myringosclerosis) in Chronic Otitis Media (COM) patients. This study aims to determine the relationship between AAA space obstructions with myringosclerosis using CT-Scan for an objective result. Methods: Retrospective study with case-control approach used in this study. Case criterias are Chronic Suppurative Otitis Media (CSOM) patients with myringosclerosis, both men and women and age 15-50 years, while the control group are benign CSOM patients without myringosclerosis. Data were analyzed with the chi-square test to prove the association between the AAA space status and length of symptom onset with myringosclerosis. Results: During January 2017-December 2019 there were 33 respondents, 19 cases and 14 controls, 21 men and 12 women with an average age of 35 years (cases) and 23.5 years (control). The length of symptom onset more than 5 years (p <0.05, OR 6.94 with CI 0.5-1.5) and AAA space obstruction (p <0.05 OR 34.25 with CI 0.8-1.8) has been shown to be associated with myringosclerosis in people with benign CSOM. Conclusions: AAA space obstruction and symptom onset more than 5 years significantly associated with myringosclerosis.